Combining a Brain–Machine Interface and an Electrooculography Interface to perform pick and place tasks with a robotic arm - Hortal, Enrique; Iáñez, Eduardo; Úbeda, Andrés; Perez-Vidal, Carlos; Azorín, José M. (Robotics and autonomous systems, 2015)
This paper presents a multimodal Human–Machine Interface system that combines an Electrooculography Interface and a Brain–Machine Interface. This multimodal interface has been used to control a robotic arm to perform pick and place tasks in a three dimensional environment. Five volunteers were asked to pick two boxes and place them in different positions. The results prove the feasibility of the system in the performance of pick and place tasks. By using the multimodal interface, all the volunteers (even naive users) were able to successfully move two objects within a satisfactory period of time with the help of the robotic arm. •A multimodal HMI to perform pick and place tasks with a robotic arm is presented.•The EOG interface is applied to control planar movements and to operate the gripper.•The BMI is used to control the height of the gripper through two mental tasks.•The system had been tested by five healthy subjects.•The results prove the feasibility of the system in the performance of these tasks.